Smart-Vehicle Retrieval System - Saravanan P, Anbuselvi M, Rohith Kumar, VasanthaSelvam (International Journal of Advanced Science and Technology, 2020)
Technology enhances the human living with comfort and less effort. In today’s world, majority of people travel by vehicles, the cities have reached their full occupancy. This reflects on the scenario, where most of the time people spend their crucial time in searching their vehicle at the parking lots. The inevitable growth of artificial intelligence and machine learning provides the supporting hand in the field of self-driving cars. In this research work, a Smart- vehicle Retrieval System which arrives at that user location from anywhere in the parking lot has been proposed. The system comprises of a machine learning algorithm to detect vehicles, support navigation with collision avoidance and lane detection strategies. The work mainly focuses on time optimization in vehicle search at the parking lot and also reducing the overall cost by improving the software techniques.